Endangered man and the solution of the Christian from the point of view of education* - Kruger, H. B. (Koers, 1979)
In this paper we are going to deal with a number of concepts and problems: endangered man and the Christian solution — from the viewpoint of education. The theme in its entirety is qualified by the contextual approach from the educational angle. The paper will thus deal specifically with those aspects of great significance for the science and practice of education.